KEANEKARAGAMAN JENIS BENALU PEMARASIT PADA TANAMAN DI KEBUN RAYA BATURRADEN DAN SEKITARNYA - ., Sunaryo; Uji, Tahan (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Benalu is one of the parasitic plant group which have been ataccked to many plantsspecies in Baturraden Botanical Garden and its vacinity. Exploration and collection ofÃ‚Â parasitic plants species in this area are conducted. Five parasitic plants species, i.e.Dendropthoe curvata, Dendropthoe pentandra, Macrosolen cochinchinensis, ScurrulaÃ‚Â lepidota and Scurrula parasitica are recorded to parasiting 18 plants species in thisÃ‚Â area. Dendropthoe pentandra is reported as the highest population species to parasitingÃ‚Â plants species. While the plants species of Myrtaceae and Lauraceae families are alsoÃ‚Â reported as the highest species parasited.Key words : diversity Ã¢â‚¬â€œ mistletoe Ã¢â‚¬â€œ Baturraden Botanic Garden and its vacinity